On lag controllers: Design and implementation - Teixeira, MCM; Assuncao, E. (Institute of Electrical and Electronics Engineers (IEEE), 2002)
Sometimes it is inconvenient or expensive to open the loop of a system to insert lag controllers-for instance, when this system is an open-loop system. A new controller structure where the loop is not opened, and that allows the design of lag controllers as in the case where one can open the loop, is presented. This result can be used by educators in undergraduate courses that deal with classic control system theory, because it allows a better comprehension of the concept of lag compensation and provides a new method for its design and implementation. An example illustrates the application of the proposed method.
Keywords: classical control; frequency response; lag controllers; root locus; transfer functions